2018
DOI: 10.1017/aaq.2018.14
|View full text |Cite
|
Sign up to set email alerts
|

Three Generations Under One Roof? Bayesian Modeling of Radiocarbon Data From Nunalleq, Yukon-Kuskokwim Delta, Alaska

Abstract: This article presents the results of a program of radiocarbon dating and Bayesian modeling from the precontact Yup'ik site of Nunalleq (GDN-248) in subarctic southwestern Alaska. Nunalleq is deeply stratified, presenting a robust relative chronological framework of well-defined individual house floors abundant in ecofacts suitable for radiocarbon dating. Capitalizing on this potential, we present the results of one of the first applications of Bayesian statistical modeling of radiocarbon data from an archaeolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 25 publications
0
25
0
5
Order By: Relevance
“…Phase II followed another phase of remodelling (occurring between cal AD 1640-1660), and is estimated to have been shorter, at a maximum of twenty-five years. Samples utilized here originate from house floors related to the occupation events associated with Phase III and Phase II, known as Event H (Phase III) and Event F (Phase II) (Ledger et al 2018).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Phase II followed another phase of remodelling (occurring between cal AD 1640-1660), and is estimated to have been shorter, at a maximum of twenty-five years. Samples utilized here originate from house floors related to the occupation events associated with Phase III and Phase II, known as Event H (Phase III) and Event F (Phase II) (Ledger et al 2018).…”
Section: Methodsmentioning
confidence: 99%
“…More recent field seasons (2013-2015) focused on Area A and a midden (Area B), and employed single context recording. This approach has allowed a site matrix to be produced (see Branch et al 2005, 34), which has in turn enabled an advanced programme of radiocarbon dating that includes Bayesian modelling (Ledger et al 2018), identifying and dating successive phases of construction, occupation, and remodelling events at the site. Zooarchaeological analysis of material from the more recent research excavations have revealed possible diachronic trends in resource procurement and use across these different occupation events, particularly regarding the proportion of fish and marine mammals (see Figure 1; adapted from Masson-MacLean et al 2019, Figure 4).…”
Section: Mots-clésmentioning
confidence: 99%
See 1 more Smart Citation
“…The most compelling case studies often report dates of events at "generational" precision (multi-decadal but sub-centennial uncertainty at 68% or 95% probability), or even better (e.g. Marciniak et al 2015;Ledger et al 2018), but it is harder to find examples of generational precision for sequences located entirely on calibration plateaus, such as the "Hallstatt plateau" (800-400 cal BC) (e.g. Hamilton et al 2015).…”
Section: Bayesian Chronological Modeling and The Calibration Curvementioning
confidence: 99%
“…The Nunalleq archaeological site is a Thule-era Yup'ik village comprised of a large sod house complex inhabited from approximately AD 1570 to 1675, likely spanning three generations (Ledger et al 2018). The nearly year-round occupation of the site (McManus-Fry 2015) and the remarkably well-preserved artifacts, ecofacts, and features found there allow us to explore questions of gender and social life that are often difficult to access in other archaeological contexts.…”
Section: Gender and Subsistence At Nunalleqmentioning
confidence: 99%